Analysis of Deformation Characteristics of Long-Short Pile Composite Foundation in Salt Lake Area, Iran. (5th December 2019) - Liu, Wei; Yang, Xiaohua; Zhang, Shasha; Kong, Xiangxin; Chen, Weizhi
Abstract : To study the settlement and deformation characteristics of a long-short pile composite foundation and its influencing factors, the indoor centrifuge model test and numerical simulations were performed under the actual working conditions to treat the saline soft soil foundation in the Soltan salt lake area of Iran. Firstly, the settlement of a long-short pile composite foundation and the law of pile-soil stress ratio development with time were studied using a centrifuge model test. In addition, FLAC3D was used to simulate the test conditions, and it has been observed that the numerical and experimental results were in good agreement. Based on the numerical model, the effects of the replacement rate of long and short piles, cushion modulus, and pile length on the settlement of the composite foundation and the stress ratio of long and short piles were analyzed. The results show that the long-short pile composite foundation can effectively control settlement. Compared to the untreated foundation, the total settlement of a long-short pile composite foundation was reduced by 67%, and the postconstruction settlement was reduced by 47.7%. Compared to the final settlement of the composite foundation obtained using the centrifuge model test, the error range of the numerical simulation results was between 2.4% and 8%. The influence of pile spacing on the settlement and stress characteristics of a long-short pile composite foundation is greater than that attributable to the arrangement of the piles. Under this geological condition, it is reasonable to choose a pile spacing of 4 d ∼5 d . When the long pile reaches the bearing stratum, the length of the short pile should not exceed 0.6 times the length of the long pile. The setting cushion not only reduces uneven settlement of the composite foundation but also improves the joint bearing capacity of the pile and the soil between the piles.